A microporous metal–organic framework with naphthalene diimide groups for high methane storage. Issue 12 (3rd July 2019) - Ye, Yingxiang; Lin, Rui-Biao; Cui, Hui; Alsalme, Ali; Zhou, Wei; Yildirim, Taner; Zhang, Zhangjing; Xiang, Shengchang; Chen, Banglin
Abstract : A microporous metal–organic framework with open metal and carbonyl sites for high methane storage at room temperature. Abstract : We reported a microporous MOF FJU-101 with open naphthalene diimide functional groups for room temperature (RT) high methane storage. At RT and 65 bar, the total volumetric CH4 storage capacity of 212 cm 3 (STP) cm −3 of FJU-101a is significantly higher than those of the isoreticular MFM-130a and UTSA-40a. The enhanced methane uptake in FJU-101a is attributed to the polar carbonyl sites, which can generate strong electrostatic interactions with CH4 molecules.